2006
DOI: 10.1055/s-2006-944661
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal endoscopy does not reassure patients with functional dyspepsia

Abstract: In patients with functional dyspepsia, upper gastrointestinal endoscopy does not improve psychological well-being or health-related quality of life. In view of the invasiveness, cost, and potential harm associated with endoscopy, careful consideration should be given to whether this procedure should be carried out merely for the sake of the patient's "peace of mind".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 15 publications
(21 reference statements)
0
17
0
2
Order By: Relevance
“…Bytzer et al [23] concluded that prompt endoscopy in the management of dyspepsia leads to no difference in terms of quality of life after 1 year. In a previous study in which we com− pared anxiety, depression, and quality−of−life scores before and 1 month after upper gastrointestinal endoscopy in patients with an organic disorder and in patients without any organic disorder, we found no relevant improvements in any of these factors [24]. This large, endoscopy−based study provides an impression of how decisions are made in real clinical practice.…”
mentioning
confidence: 45%
“…Bytzer et al [23] concluded that prompt endoscopy in the management of dyspepsia leads to no difference in terms of quality of life after 1 year. In a previous study in which we com− pared anxiety, depression, and quality−of−life scores before and 1 month after upper gastrointestinal endoscopy in patients with an organic disorder and in patients without any organic disorder, we found no relevant improvements in any of these factors [24]. This large, endoscopy−based study provides an impression of how decisions are made in real clinical practice.…”
mentioning
confidence: 45%
“…Several "before and after" studies have been published concerning the effect of HP eradication on quality of life. (120)(121).…”
Section: Hp Infection: Eradication and Effect On Well-being And Qualimentioning
confidence: 99%
“…Ayurveda recognizes this condition is one of the major digestive disorders like Amlapitta or Vidagdhajirna that result due to dysfunction of Jatharagni, or the Agni situated in upper part of digestive system and identifies etiological factors like indulgence of incompatible foods, irregular food habits and seasonal variations for it. 6,7 Treatment of functional dyspepsia remains problematic. Historically, the H2-receptor antagonists have been tried but the results are disappointing.…”
Section: Introductionmentioning
confidence: 99%